2016
DOI: 10.1186/s12891-016-1240-3
|View full text |Cite
|
Sign up to set email alerts
|

Injury patterns of the acromioclavicular ligament complex in acute acromioclavicular joint dislocations: a cross-sectional, fundamental study

Abstract: BackgroundHorizontal instability impairs clinical outcome following acute acromioclavicular joint (ACJ) reconstruction and may be caused by insufficient healing of the superior acromioclavicular ligament complex (ACLC). However, characteristics of acute ACLC injuries are poorly understood so far. Purposes of this study were to identify different ACLC tear types, assess type-specific prevalence and determine influencing cofactors.MethodsThis prospective, cross-sectional study comprised 65 patients with acute-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 29 publications
(62 reference statements)
3
35
0
Order By: Relevance
“…1,2,3,16,20,23,26 All cases in our cohort group illustrated injury of the superior AC ligament. Similar to findings of a prior surgical prospective study investigating morphologic patterns of AC ligament tears in patients with highgrade ACJ injuries, 14 we observed a majority of superior (79%) and inferior AC ligament tears (88%) anatomically involving their clavicular insertions. This morphologic pattern of AC ligamentous injury, particularly involvement of the anterosuperior AC ligament and implications for anteroposterior stability of the joint, may be an important consideration in precise preoperative planning in the setting of high-grade ACJ injuries where AC ligament disruption and incarceration may prevent anatomic ACJ reduction and necessitate open versus arthroscopic ACJ surgical reduction and reconstruction.…”
Section: Discussionsupporting
confidence: 88%
“…1,2,3,16,20,23,26 All cases in our cohort group illustrated injury of the superior AC ligament. Similar to findings of a prior surgical prospective study investigating morphologic patterns of AC ligament tears in patients with highgrade ACJ injuries, 14 we observed a majority of superior (79%) and inferior AC ligament tears (88%) anatomically involving their clavicular insertions. This morphologic pattern of AC ligamentous injury, particularly involvement of the anterosuperior AC ligament and implications for anteroposterior stability of the joint, may be an important consideration in precise preoperative planning in the setting of high-grade ACJ injuries where AC ligament disruption and incarceration may prevent anatomic ACJ reduction and necessitate open versus arthroscopic ACJ surgical reduction and reconstruction.…”
Section: Discussionsupporting
confidence: 88%
“…The authors classified AC ligament lesions into 1 of 4 types based on tear pattern—clavicular-sided, oblique, midportion, or acromial-sided—and hypothesized that understanding the type of tear could lead to improved healing and lower rates of recurrent horizontal instability after reconstruction. 27…”
Section: Resultsmentioning
confidence: 99%
“…9 This may not be easily pinpointed intraoperatively, as previous studies have shown the ACLC to have several variations of anatomy and injury pattern (clavicle-sided, oblique, midpoint, and acromion-sided ACLC tear) in an acute AC dislocation. 30,31 Moreover, in chronic and revision cases, the ACLC may be irreparable and reconstruction may be necessary. In contrast to the current technique described, the obvious downside of the dermal allograft include an inherent additional monetary cost, along with the potential for added stress to the distal clavicle to potentially fracture.…”
Section: Discussionmentioning
confidence: 99%